PEMANFAATAN EKSTRAK JAHE MERAH(Zingiber officinale var. Rubrum) DAN KULIT NANAS(Ananas comosus L. Mer) DALAM PEMBUATAN BUBUK INSTAN - Ahmad Dawardi Harahap; Raswen ' Efendi; Noviar ' Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The research purposes was to evaluate of the quality and antioxidant of the instant powder of red ginger with the addition of skin pineapples extracts. The method used in this research was a Complete Random Design with 4 treatments and 4 replications. The treatments were P1 (90 mlred ginger extracts : 10 mlskin pineapples extracts), P2 (80 mlred ginger extracts : 20 mlskin pineapples extracts), P3 (70 mlred ginger extracts : 30 mlskin pineapples extracts), P4 (60 mlred ginger extracts : 40 mlskin pineapples extracts). The results show that the usage red ginger and skin pineapples extracts significantly influenced the total sugar content,antioxidant, descriptive value of aroma and taste of instant powder, but did not affect the moisture and ash contents, color, and texture of instant powder. The best treatment was P4 (60% red ginger extracts : 40%  skin pineapples extracts)with total sugar content of 61,29%, ash content 1,44%, moisture content 1,68% and antioxidant 33,701ppm. For the quality attributes like color, flavor, taste, texture, and overall assessment with descriptive color whitey-brown, flavorfull pineapple, taste pineapple and texture rather smooth and comply with quality standards instan powder, base on the parameters of  mouisture content, ash content and total sugar content. Keyword :Instant powder, quality, skin pineapples extracts, red ginger.